Effect of a dynamic loaded warm-up on vertical jump performance - Chattong, C.; Brown, L. E.; Coburn, J. W.; Noffal, G. J. (The Journal of Strength and Conditioning Research, 2010)
Considering the importance of the vertical jump in several sports, an optimal warm-up protocol may help athletes perform at their maximum level. The purpose of this study was to investigate the potentiating effects of different levels of external resistance (weighted vest) during box jumps on vertical jump performance. Twenty resistance trained men (age 22.45 ± 1.73 years, height 176.83 ± 6.67 cm, mass 76.98 ± 8.56 kg) participated in this study. Subjects performed 5 jumps onto a box equivalent in height to their lateral femoral condyle. After a 2-minute rest period, subjects performed 3 vertical jumps with the greatest height being recorded. On day 1, each subject performed a control condition with no external resistance to establish a baseline vertical jump height. On the following days, they performed 4 random jump conditions with a weight vest equivalent to 5, 10, 15, or 20% of their body weight then rested for 2 minutes before performing 3 posttest vertical jumps. Results demonstrated no significant interaction of condition by time for vertical jump height. However, there was a significant main effect for time (p < 0.05) with posttest jump height (22.99 ± 3.35 in.) being greater than pretest jump height (22.69± 3.37 in.). Performing an active dynamic warm-up with or without a weighted vest produced significantly greater posttest vertical jump performance. A dynamic warm-up may improve vertical jump performance, albeit to a very small increment.